ANALISIS PESAN DAKWAH DALAM LIRIK LAGU SEBELUM CAHAYA KARYA BAND LETTO: Studi Analisis Semiotika Ferdinand De Saussure - Hadi Ismanto; Achmad Naufal Hanif Pasaribu (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
Islam is a religion that calls on its people to carry out da'wah, one of the da'wah carried out by the Letto band group is da'wah using music, at first glance the band's work is only limited to works about human romance with humans but if examined the song contains many da'wah messages, therefore. This research aims to: Knowing the results of the Analysis of the Song